2021
DOI: 10.1007/s40123-021-00373-y
|View full text |Cite
|
Sign up to set email alerts
|

A Narrative Review of Current Understanding and Classification of Dry Eye Disease with New Insights on the Impact of Dry Eye during the COVID-19 Pandemic

Abstract: Dry eye disease (DED) is a complex, progressive and multifactorial condition that is commonly seen in clinical practice and can be challenging to accurately diagnose. Untreated or suboptimally managed dry eye can progress to severe, chronic disease which may become resistant to treatment. Symptoms include ocular irritation and visual impairment. Patients frequently report negative consequences regarding quality of life (QoL), productivity and psychological wellbeing. Certain lifestyle factors (e.g. use of scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 58 publications
2
13
0
1
Order By: Relevance
“…According to a recent European survey report, increased mental stress and poor sleep quality were listed in the top three most common causes of worsening DED symptoms during the lockdown. [37] This result was consistent with studies which had found an association between psychiatric problems and DED. [15][16][17][18][19][20] The reason is that the perception of dry-eye symptoms was influenced by several psychological traits, such as anxiety and depression.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…According to a recent European survey report, increased mental stress and poor sleep quality were listed in the top three most common causes of worsening DED symptoms during the lockdown. [37] This result was consistent with studies which had found an association between psychiatric problems and DED. [15][16][17][18][19][20] The reason is that the perception of dry-eye symptoms was influenced by several psychological traits, such as anxiety and depression.…”
Section: Discussionsupporting
confidence: 92%
“…[36] The findings were consistent with that of a European survey, which reported that increased screen time was significantly associated with worsening dryeye symptoms in DED respondents. [37] Although previous research predominantly focused on overall VDT exposure during the lockdown, our results revealed details about the purposes of the daily VDT usage. This study confirmed that the overall VDT exposure was greater during the lockdown.…”
Section: Discussionmentioning
confidence: 67%
“…The participants in that investigation also suffered with dry-eye symptoms, which eventually led to a reduction in their work efficiency 37 . The findings were consistent with that of a European survey, which reported that increased screen time was significantly associated with worsening dry-eye symptoms in DED respondents 38 . Although previous research predominantly focused on overall VDT exposure during the lockdown, our results revealed details about the purposes of the daily VDT usage.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the current investigation revealed that having mental health problems correlated with having more severe dry-eye symptoms (a DESS of less than 75) during the lockdown. According to a recent European survey report, increased mental stress and poor sleep quality were listed in the top three most common causes of worsening DED symptoms during the lockdown 38 . This result was consistent with studies which had found an association between psychiatric problems and DED 15 – 20 .…”
Section: Discussionmentioning
confidence: 99%
“…За даними японських дослідників [18] групу ризику для «синдрому сухого ока» серед користувачів візуальних цифрових дисплеїв становлять жінки, користувачі старші 30 років та користувачі, які проводять більше 8 годин за відеотерміналами. Результати масштабного європейського дослідження [19], проведеного в період першої ізоляції (березень-вересень 2020 року), свідчать, що збільшення часу перегляду екрану в значній мірі сприяють погіршенню симптомів «сухого ока». Крім цього, «синдром сухого ока» часто супроводжує інші порушення зору.…”
Section: Scientific Collection «Interconf» | № 95 503unclassified